The Effect of Zinc Supplementation on Pneumonia In Hospitalized Patients Aged 1-60 Months (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background: One of the important causes of pediatric deaths in underdeveloped countries is Pneumonia and to reach the fourth Millennium Development Goa which aimed at reducing the under-five mortality rate. Study the effect of zinc as optional therapy on duration until normalization of respiratory rate, temperature, oxygen saturation, feeding, chest auscultation, and duration of hospitalization in Babylon Teaching Hospital for Gynecology and Pediatrics.Objectives: To evaluate the effect of zinc supplementation as an adjunctive therapy on the outcome of  pneumonia.Patients and Methods: In a hospital-based cross-sectional study in Babylon Teaching hospital for Gynecology and Pediatrics, two hundreds children aged between one month and 60 months with pneumonia had been followed, one hundred patients received  zinc in addition to their treatment (10 mg for patients their ages  six months or below , and 20 mg for those whowere older than 6 months of age) during the days of hospitalization, and the other one hundred received their treatment without zinc. The clinical symptoms and signs  of pneumonia had been detected and documented at time of admission, after24hours  , 72hours ,and after 120 hours .Results: From the medical history there were significant differences(p value ≤ 0.05) regarding duration of pneumonia , but there were no significant differences regarding type of feeding or body weight. Females benefited more than males. There were clinical and statistically significant difference  ( p. value ≤ 0.05) in the patient's clinical condition regarding  duration of hospitalization, improvement of temperature, chest in drawing, audible wheeze, feeding, and fate (discharge or ICU admission), but there were no significant differences regarding consciousness level, SpO2, and chest auscultation.Conclusions: Zinc supplementation in patients with pneumonia reduces the noumber of admission to the hospital and hastens the improvement regarding temperature, chest indrawing, audible wheeze, feeding, and reduces ICU admission . Females  benefit was more than males'.